Efficacy and safety of antitumor agents plus radiotherapy compared with radiotherapy alone for brain metastases from lung cancer - Lin, Heng (Mol Clin Oncol, 2017)
The present study aimed to investigate the efficacy and safety of different therapeutic regimens for brain metastases (BMs) from lung cancer (LC). A total of 13 controlled trials (1,783 cases) involving chemotherapy, tyrosine kinase inhibitors or endostatin plus radiotherapy (combination group) vs. radiotherapy alone group were identified from PubMed. Compared with the radiotherapy alone group, the combination group resulted in a significant benefit for objective response rate (ORR) [risk ratio (RR), 1.38; 95% confidence interval (CI), 1.19–1.60; P<0.0001], notably prolonged the time to central nervous system progression [CNS-TTP; hazard ratio (HR), 0.71; 95% CI, 0.57–0.90; P=0.004] and progression-free survival (PFS; HR, 0.60; 95% CI, 0.44–0.83; P=0.002); however, failed in prolonging the overall survival (OS; HR, 0.80; 95% CI, 0.61–1.05; P=0.11) with a higher overall severe adverse events (AEs, Grade ≥3; RR, 2.57; 95% CI, 1.24–5.35; P=0.01). Notably, subgroup analysis demonstrated that targeted therapy plus radiotherapy possessed a superior OS compared with radiotherapy alone (HR, 0.58; 95% CI, 0.37–0.90; P=0.01) with mild non-hematological toxicity and without severe hematotoxicity. The present study demonstrated that targeted agents plus radiotherapy possessed desirable effects with mild adverse events. Secondary to best, chemoradiotherapy is an alternative option for patients without suitable molecular targets.